First data on the geochemistry of fluvial deposits of Caybagi and Palu formations (Eastern Elazig, Turkey) - Bal Akkoca, Dicle; Yildirim, Ismail; Erturk, Mehmet Ali (Pamukkale Univ, 2018)
In this study, the geochemistry (major, trace and rare earth elements) of fluvial deposits of the Caybagi and Palu Formations, Eastern Elazig, have been investigated. The basement of the studied basin is composed of the Guleman Group, Elazig Magmatics, Hazar-Maden Group, and Kirkgecit Formation which consist of volcanic materials derived from the Elazig Magmatics. The Caybagi Formation is composed of thick fluvio-lacustrine sedimentary sequence. Palu Formation consists of alluvial fan deposits and braided river, lacustrine sedimentary deposits. Samples were collected from braided river deposits of Caybagi and Palu Formation along Hacisamdere-Caybagi section (C-samples) and Hacisamdere-Palu section (PL samples). Significant positive correlation between Zr/Sc and Th/Sc ratios of two sample groups show that the siliciclastic sample groups do not represent considerable sediment recycling. Caybagi and Palu samples have similar geochemical indices (Al2O3/TiO2, Ti/Zr, La/Th, La/Sc, Cr/Th, Co/Th, (La/Yb)(N), (Gd/Yb)(N), LREE/HREE ratios) and indicate derivation from intermediate-basic source rocks. In Si vs. Na/K diagram samples plot in arc field and La/Sc and Ti/Zr ratios show that samples were plotted in an oceanic island arc environment.
Keywords: Elazig; Fluvial deposits; Geochemistry; Tectonic setting